Contributions of Social and Psychological Assessments in Juvenile Justice Decision Making in Portugal: A Document Analysis - Pessanha, Elisabete (2023)
This study aims to analyze the contribution of social and psychological assessments in juvenile justice decision making in pre and post sentencing phases. For this purpose, 30 court cases of young people aged between 12 and 16 have been consulted. Document analysis was conducted through an analytic grid. The results indicate that the judges agree with 93,3% of socio-educational measures suggested by the social technicians/forensic psychologists. Towards the review of socio-educational measures, it is observed a high correspondence (87,5%) between technical suggestions (socio-educational measures) and the implementation of judicial measures. The frequency of interactions between technicians and judges in the post sentencing period rounds 73,3%. Therefore, it is noticed a consistent cooperation between judges and social technicians/forensic psychologists throughout the process, as well as the acknowledgment by the judges of the competence and technical knowledge of social technicians.